2007
DOI: 10.1902/jop.2007.060332
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Pressure and Vasculature of Gingiva in Experimental Diabetes Mellitus

Abstract: Our results reveal that the fluid dynamics of periodontal soft tissues may be affected by the diabetic conditions in this diabetic model because of the increased OP and VN during the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Further local changes observed in diabetes conditions include an increased osmotic pressure and increased number of vessels in the gingival tissues , as well as enhanced basal membrane thickness in gingival capillaries and venules correlating with the duration of the diabetes .…”
Section: Further Local Changesmentioning
confidence: 99%
“…Further local changes observed in diabetes conditions include an increased osmotic pressure and increased number of vessels in the gingival tissues , as well as enhanced basal membrane thickness in gingival capillaries and venules correlating with the duration of the diabetes .…”
Section: Further Local Changesmentioning
confidence: 99%
“…2005 , 42 , 277−345; J. Periodontol. 2007 , 78 , 757−763) and water transport in plants. It is also involved in many technological applications such as drug delivery systems ( Crit.…”
mentioning
confidence: 99%
“…Using experimental rat model for diabetes Sakallioglu et al . [ 28 ] evaluated the osmotic pressure and vascular diameter in gingival tissues and proposed a correlation between these two parameters. The authors also suggested the need to investigate the vascular changes in diabetic humans as their study involved only experimentally induced rat model.…”
Section: Discussionmentioning
confidence: 99%